Penerpan Metode Waterfall Pada Perancangan Sistem Informasi Koperasi Simpan Pinjam Berbasis Web Menggunakan Php Dan MySQL - Priono, Joko; Latifah, Fitri (Journal of Information System, Informatics and Computing, 2024)
Credit Unions aim to collectively meet the economic needs of members based on Credit Union principles. KSP CU SAN-YOS MITRA SEJATI, as one of the credit unions that adhere to these principles, also provides savings and loan services. Currently, management and registration at KSP CU SAN-YOS MITRA SEJATI is still done manually by registering in books and using Microsoft. Excel. Additionally, submitted reports are often late. To overcome this problem, KSP CU SAN-YOS MITRA Credit Union needs an information system that should make it easier for directors, supervisors and management to manage KSP CU SAN-YOS MITRA SEJATI and increase member confidence. Savings and Credit Cooperative Information System is designed using waterfall method and supports web operations of KSP CU SAN-YOS MITRA SEJATI with PHP as programming language and MySQL as database . With this information system, data processing becomes easier, more efficient and more careful, and reports can be presented more quickly and accurately.